A retrospective study of microwave ablation and thoracoscopic surgery for multiple primary lung cancer: a propensity score matching analysis - Li, Bangsheng; Gao, Shengguai; Mao, Jie; Yang, Zhenghong; Chen, Ying; Wang, Xi; Huang, Yunchao (Frontiers in Surgery, 2025)
PurposeMicrowave ablation (MWA) is a minimally invasive local treatment with demonstrated safety and efficacy, but its role in managing multiple primary lung cancer (MPLC) is not well-established. This study retrospectively evaluates the clinical effectiveness of MWA compared to video-assisted thoracoscopic surgery (VATS) in treating MPLC.Materials and methodsA retrospective analysis was conducted using data from patients with non-small cell lung cancer (NSCLC) treated at Peking University Cancer Hospital Yunnan Hospital between January 2021 and April 2024. All patients had undergone surgical resection for their first primary lung cancer (FPLC) and subsequently received either MWA or VATS for second primary lung cancer (SPLC). After 1:1 propensity score matching (PSM), 202 patients per group were included. Study endpoints included progression-free survival (PFS), overall survival (OS), complications, and pulmonary function changes.ResultsMedian follow-up was 24.47 months. Survival analysis revealed a statistically significant difference in PFS between MWA and VATS groups (HR = 2.74, 95% CI: 1.40–5.36, p = 0.006), while OS showed no difference (HR = 1.41, 95% CI: 0.45–4.36, p = 0.56). The incidence of grade ≥ II complications was significantly lower in the MWA group (p < 0.001). Pulmonary function tests indicated no significant changes in forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1), FEV1%, maximal voluntary ventilation (MVV), and diffusion capacity of the lung for carbon monoxide%(DLCO%) before and 1–3 month post MWA (p > 0.05).ConclusionsIn MPLC patients with stage IA SPLC, VATS demonstrates a greater clinical efficacy advantage in terms of local tumor control compared to MWA. Additionally, MWA provided significant advantages in reducing complication severity and preserving pulmonary function. These findings suggest that the therapeutic approach combining surgery with MWA represents a safe and effective option for MPLC.